Estudo da reação de remoção do monóxido de carbono com catalisadores industrial e sol-gel à base de cobre - Ferrari, Tatiane Caroline (2015)
The water gas shift reaction (WGSR), has been widely used as a way to remove the poisonous CO from the hydrogen current from methanol reforming. In this study, Cu/ZnO/ Al2O3 catalysts were used to study this reaction. The catalysts used were commercial HiFUEL W220 and one prepared by the sol-gel method. The materials were dried, and the calcination temperature was determined by DSC-TGA analysis. The materials were calcined and characterized according to the BET area, pore diameter and pore volume, TPR, S-TPR, XRD, TPD, SEM. After calcination, the catalysts were loaded into the reactor, then reduced and tested in the WGSR at low temperatures (200-250°C). Long duration tests have been performed (in which the temperature and the CO/steam molar ratio were kept at 200°C and 1/2, respectively). Short duration tests have been carried out temperature (between 200 and 250°C) and CO/steam molar ratio (between 1/4 and 1/2). Conversion of CO and H2 yield were examined. Gaseous and liquid products leaving the reactor were analyzed by gas chromatography. CO2 and H2 were produced, along with small quantities of coke. The conversions obtained for the long-term tests were higher when the catalyst synthesized by the sol-gel method was used. The coke was analyzed by SEM for the industrial catalyst. A carbon balance for identification of coke was also carried out. According to this carbon balance, the sol-gel catalyst yielded less. A mathematical model was developed for a CO reduction reactor and four kinetic expressions from the literature have been applied to this model (elementary, AYASTUY et al. (2005), AMADEO and LABORDE (1995), and Criscuoli et al. (2000)). The proposed mathematical model was solved in MATLAB. The behavior obtained for the CO conversion were compared with experimental data. The kinetics showed a better fit for the sol-gel catalyst data was proposed by AYASTUY et al. (2005) to the molar ratios CO / water vapor ½ and 1/3 and proposed by Criscuoli et al. (2000) molar ratio to 1/4. In the best results obtained for the same contact time, the reactor was determined length required for the CO concentration decreases to 4000 mg L-1, which according MENECHINI Neto et al. (2014) is the average concentration of CO at the exit of a reactor for methanol steam reforming, CO to the acceptable limit for application in fuel cells (50 mg L-1).